CHILDREN’S FICTION AS AN IDEOLOGICAL STATE APPARATUS: ANALYZING SELECTED BRITISH SHORT STORIES FOR CHILDREN AS WORKS OF COLONIAL LITERATURE - Anwaar, Tayyaba Fatima; Dr Amara Khan (Journal of Arts & Social Sciences, 2022)
Building upon select short stories by Enid Blyton and Rudyard Kipling, this research aims to explore propagation of the imperialist ideology through British short stories for children. The select stories are examined as part of the discourse developed to glorify Britain and depreciate its colonized subjects. The study discusses the stories as they explore colonization in light of the theories developed in the Metropole. Keeping in view that children’s fiction promotes various ideologies, this research argues that short stories for children may become an immensely significant medium in fostering the imperialist ideology, thus functioning as Ideological State Apparatuses through the very important learning years of childhood. For this purpose, the theoretical framework of Ideological State Apparatuses by Louis Pierre Althusser has been employed. This incorporation serves to elucidate the role of educational ISAs in shaping the minds of children from early childhood. Children’s indoctrination in such manner may produce new generations of people that might support the colonialist stance both knowingly or unknowingly. A useful strategy to counter this situation is writing back to the Empire by producing children’s books that function as sights of decolonization. The real challenge, however, is to make de-colonial literature accessible to young minds around the globe.